Konsekuensi dari Brand Association dan Brand Awareness pada E-Commerce Application di Indonesia - Audya Silvy Aulya (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to examine and analyze the role of brand association and brand awareness to customer loyalty, and brand association to willing to pay in e-commerce applications from consumers. The number of samples used in this research were 202 respondents. Purposive sampling technique is the technique used in this research. Data were analyzed using the Structural Equation Model (SEM) method. The results of this study are: (1) Brand association has a positive impact on customer loyalty, (2) brand awareness has a positive impact on customer loyalty, and (3) halal brand association has a positive impact on willing to pay.